Analisis Cedera Olahraga Dalam Aktivitas Pendidikan Jasmani Pada Siswa SMA Negeri 1 Nalumsari - Supriyadi, Hery; Supriyono, Supriyono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this study is: To determine the body that are often exposed to injury and the cause of injury to the physical education sports activities in SMAN 1 Jepara regency Nalumsari academic year 2015/2016. The method used is quantitative descriptive. The technique of collecting data using questionnaires, interviews, observation, and documentation. The results of the 84 number of students who suffered an ankle injury (38 students), the fingers (34 students), toe (28 students) of the head, neck and wrist (26 students), calves (22 students), chest (18 students) , shoulders, elbows, back (16 students) and thighs (10 students). The cause of the injury is the movement of the body mistakenly (44 students), physical condition declined (38 students), bumping bodies with friends (34 students), lack of warm (32 students), the movement of excess body (30 students) body condition unfit (26 students ), the length of the body that are not the same (24 students) and trauma due to injury never happened (20 students) .Simpulan of students of SMA Negeri 1 Nalumsari Jepara students are exposed parts of the body most injured an ankle injury that caused excessive body movement.